Hierarchical Control of Nitrite Respiration by Transcription Factors Encoded within Mobile Gene Clusters of Thermus thermophilus - Alvarez, Laura (Genes (Basel), 2017)
Denitrification in Thermus thermophilus is encoded by the nitrate respiration conjugative element (NCE) and nitrite and nitric oxide respiration (nic) gene clusters. A tight coordination of each cluster’s expression is required to maximize anaerobic growth, and to avoid toxicity by intermediates, especially nitric oxides (NO). Here, we study the control of the nitrite reductases (Nir) and NO reductases (Nor) upon horizontal acquisition of the NCE and nic clusters by a formerly aerobic host. Expression of the nic promoters PnirS, PnirJ, and PnorC, depends on the oxygen sensor DnrS and on the DnrT protein, both NCE-encoded. NsrR, a nic-encoded transcription factor with an iron–sulfur cluster, is also involved in Nir and Nor control. Deletion of nsrR decreased PnorC and PnirJ transcription, and activated PnirS under denitrification conditions, exhibiting a dual regulatory role never described before for members of the NsrR family. On the basis of these results, a regulatory hierarchy is proposed, in which under anoxia, there is a pre-activation of the nic promoters by DnrS and DnrT, and then NsrR leads to Nor induction and Nir repression, likely as a second stage of regulation that would require NO detection, thus avoiding accumulation of toxic levels of NO. The whole system appears to work in remarkable coordination to function only when the relevant nitrogen species are present inside the cell.